Fungsi Lembaga Wali Nanggroe Dalam Menyelesaikan Konflik Lokal Masa Penerapan Otonomi Khusus - Amrullah Bustamam (2022)
This study discusses the existence of the Wali Nanggroe Institution as a mediator in each conflict that has different intensities. Wali Nanggroe is believed to be the institution for resolving conflicts that occurred after Aceh was peaceful, between institutions in Aceh Province. Post-peace conflicts in Aceh such as communication conflicts, politics, and other social problems between institutions and the community. However, these conflicts often arise on the grounds that the institutions that handle them do not give serious attention, sometimes even do not care at all. This study aims to examine the role of the Wali Nanggroe Institution in resolving local conflicts during the Special Autonomy imposed in Aceh. This research is a literature study using a qualitative approach which is then explained descriptively. The results of this study explain that the Wali Nanggroe Institution plays a very important role in organizing and maintaining peace in Aceh as well as its participation in the process of resolving world peace. On the other hand, the Aceh Government Law provides great legality to the role of the Wali Nanggroe Institution.